2019
DOI: 10.3390/mi10060373
|View full text |Cite
|
Sign up to set email alerts
|

A New Theoretical Approach of Wall Transpiration in the Cavity Flow of the Ferrofluids

Abstract: An idea of permeable (suction/injection) chamber is proposed in the current work to control the secondary vortices appearing in the well-known lid-driven cavity flow by means of the water based ferrofluids. The Rosensweig model is conveniently adopted for the mathematical analysis of the physical problem. The governing equation of model is first transformed into the vorticity transport equation. A special finite difference method in association with the successive over-relaxation method (SOR) is then employed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
17
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(17 citation statements)
references
References 43 publications
0
17
0
Order By: Relevance
“…In this regard, a study is reported in [29] by considering the flow inside the cavity filled with nanoliquid. The authors treated the model numerically and authenticate their results with previously published work.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, a study is reported in [29] by considering the flow inside the cavity filled with nanoliquid. The authors treated the model numerically and authenticate their results with previously published work.…”
Section: Introductionmentioning
confidence: 99%
“…The resulting dimensionless equations (12) to (15), together with boundary constraints (16), are highly nonlinear, which commences a challenge to recommend the numerical or analytical solution. The homotopy analysis method is the best analytic technique to attain a series solution of such nonlinear partial differential expressions with excellent accuracy.…”
Section: Homotopy Analysis Methodsmentioning
confidence: 99%
“…8 The interesting shape of nanoparticles influenced by Hall current, exponential heat source, and mixed convection features due to rotating frame was numerically examined by Mahanthesh et al 9 The rheological outcomes for Eyring-Powell nanomaterial with activation energy and slip impact were assessed by Alwatban et al 10 Khan et al 11 focused on the rheological features of magnetized couple stress nanofluid in which numerical simulations were performed with the implementation of shooting algorithm with convincing accuracy. Siddiqui and Turkyilmazoglu 12 considered the consequences of ferrofluids in a lid-driven cavity flow subjected to the suction/injection characteristics. The significance of chemical reaction and activation energy in the flow of magnetized Sisko nanofluid was analyzed by Ahmad et al 13 Tlili et al 14 formulated the Oldroyd-B nanofluid model with activation energy over a stretched cylinder.…”
Section: Introductionmentioning
confidence: 99%
“…However, Turkyilmazoglu [26], [27] proposed an implicit numerical scheme for solving transient flows based on the spectral Chebyshev collocation technique in the direction normal to the disk and forward marching in time, which can better solve the magnetohydrodynamic time-dependent of von Karman flow. And Abid and Turkyilmazoglu [28] employ a special finite dierence method in association with the successive over-relaxation method (SOR) to numerically simulate the flow behavior. These researches definitely provide inspirations for the numerical simulation in this paper.…”
Section: Index Termsmentioning
confidence: 99%